(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The advent of technology has revolutionized the way we interact with the world, but it has also presented unprecedented challenges to our privacy rights. As technology continues to evolve at an exponential rate, the gap between its capabilities and the existing legal frameworks designed to protect our privacy widens. This article delves into the profound impact of technology on privacy laws, exploring the challenges it poses and the urgent need for adaptation. One of the most significant challenges is the sheer volume and granularity of data that can now be collected about individuals. From online browsing histories to social media interactions, geolocation data, and even biometric information, our digital footprints are extensive and constantly expanding. This wealth of data is invaluable to businesses and governments alike, but it also raises concerns about surveillance, profiling, and the potential for misuse. Moreover, the rise of artificial intelligence (AI) and machine learning has further complicated the privacy landscape. AI-powered algorithms can analyze vast datasets to identify patterns and make predictions, often without human intervention. This raises questions about transparency, accountability, and the potential for bias in decision-making processes that can have significant consequences for individuals.